2022
DOI: 10.1021/acsabm.1c01286
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Hydrogels Containing Geraniol and Icaridin Encapsulated in Zein Nanoparticles for Arbovirus Control

Abstract: The most important arboviruses are those that cause dengue, yellow fever, chikungunya, and Zika, for which the main vector is the Aedes aegypti mosquito. The use of repellents is an important way to combat mosquito-borne pathogens. In this work, a safe method of protection employing a repellent was developed based on a slow release system composed of zein nanoparticles containing the active agents icaridin and geraniol incorporated in a cellulose gel matrix. Analyses were performed to characterize the nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Kumar et al [ 79 ] showed the promising repellent activity and delayed release of citronella-oil-microsponge-loaded hydrogel. Most recently, Rogeiro et al [ 80 ] developed nanoparticle mosquito repellent based on a slow-release system composed of zein nanoparticles containing the encapsulated active agents icaridin and geraniol incorporated in a cellulose gel matrix.…”
Section: Gels For Risk Mitigation Of Mosquitoesmentioning
confidence: 99%
“…Kumar et al [ 79 ] showed the promising repellent activity and delayed release of citronella-oil-microsponge-loaded hydrogel. Most recently, Rogeiro et al [ 80 ] developed nanoparticle mosquito repellent based on a slow-release system composed of zein nanoparticles containing the encapsulated active agents icaridin and geraniol incorporated in a cellulose gel matrix.…”
Section: Gels For Risk Mitigation Of Mosquitoesmentioning
confidence: 99%
“…Picaridin (icaridine, 1-piperidinecarboxylic acid 2-(2-hydroxyethyl)-1-methylpropylester), a cyclic amine and a member of the piperidine chemical family, is viewed as a synthetic, broad-spectrum arthropod repellent [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The repellent and deterrent activities of picaridin have been previously demonstrated to involve olfactory sensing in mosquitoes and ticks, via their interactions with odorant receptor proteins residing in neurons [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%